2015
DOI: 10.1002/ldr.2355
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Perceptions Attitudes and Responses of Winegrowers about Sustainable Land Management in Central Spain

Abstract: This study provides a better understanding of the perspective and attitudes of farmers towards sustainable land management (SLM) practices in central Spain. Farmer's willingness to change from conventional tillage to cover crops in vineyards is seen as an indicator for adoption of sustainable agriculture. Two complementary approaches were used: open interviews (n = 25) and surveys (n = 64). The portrait of these winegrowers is of mature farmers, owners of their lands and conscious of soil erosion problems (81%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 49 publications
(53 reference statements)
1
62
0
2
Order By: Relevance
“…Vineyards represent one of the most important crops in terms of income and employment, especially for three of the world's top ten grape-producing countries found in the Mediterranean region, namely Spain, Italy and France, where the total grape area in 2009 amounted to 11,000, 8020 and 8100 km 2 and thus 2.2, 2.6 and 1.5% of the respective national land areas (Anderson and Norman, 2011). For these reasons, adequate soil management practices are needed to contribute to a more sustainable viticulture, which includes evaluation to determine whether they are acceptable to the farmers who will have to utilize them (Galati et al, 2015;Marques et al, 2015). The most common soil management techniques in Mediterranean countries consist of tillage (mechanical weeding) and no-tillage (chemical weeding) operations (García-Orenes et al, 2009), and both of them generally result in bare soils during the entire year Lasanta and Sobrón, 1988;Vaudour et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Vineyards represent one of the most important crops in terms of income and employment, especially for three of the world's top ten grape-producing countries found in the Mediterranean region, namely Spain, Italy and France, where the total grape area in 2009 amounted to 11,000, 8020 and 8100 km 2 and thus 2.2, 2.6 and 1.5% of the respective national land areas (Anderson and Norman, 2011). For these reasons, adequate soil management practices are needed to contribute to a more sustainable viticulture, which includes evaluation to determine whether they are acceptable to the farmers who will have to utilize them (Galati et al, 2015;Marques et al, 2015). The most common soil management techniques in Mediterranean countries consist of tillage (mechanical weeding) and no-tillage (chemical weeding) operations (García-Orenes et al, 2009), and both of them generally result in bare soils during the entire year Lasanta and Sobrón, 1988;Vaudour et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Water scarcity is one of the most important limiting factors in agricultural semiarid regions. In central Spain, farmers relate the use of GC to water consumption and this, together with cultural reasons, generates a refuse to GC systematically (Marqués et al, 2015). Therefore, there is a need of research about the effects of GC on grape yield and must quality in representative vineyards of central Spain.…”
Section: Groundcovers: Grape and Winementioning
confidence: 99%
“…In the Madrid region, it is even lower: 3.1 % (MAGRAMA, 2015c). This is mostly due to cultural reasons and the reduction in grape yields (Marqués et al, 2015). Ruiz-Colmenero et al (2011) found that in two out of three trials, GC in rainfed vineyards reduced grape yields significantly.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations